Critical Discourse Analysis of the Image Construction of South Korean Public Figures in Online Media Detik.com - Marshella Evelyn Yolie; Lusia Savitri Setyo Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
In the digital era, mass media not only conveys information but also shapes public opinion through word choice, language style, and news construction. In the entertainment sector, this role is particularly strong as media also influence celebrities’ public image. This study examines how Detik.com constructs the image of South Korean actors in its entertainment section, focusing on Kim Soo Hyun and the late Kim Sae Ron, using Van Dijk’s critical discourse analysis alongside concepts of mass communication, media construction, and public figure image. Through a qualitative approach, the research describes the process of image formation through text structure, journalists’ social cognition, and the digital social context. Findings show that Detik.com produces news in a circular manner by repeating narratives, reactivating prior contexts, and using hyperlinks, so that an actor’s image emerges from the overall text series. Journalist’s social cognition, including ideology, experience, popular culture knowledge, and fanbase connections, influences news writing. Digital contexts such as issue virality, public moral sensitivity, and shifting knowledge authority lead media to cite unofficial sources. The study also identifies gender bias, with female figures bearing greater moral responsibility. Overall, media do not merely inform but actively shape actors’ images and public meaning.